The impact of a training program to raise worker’s skills in the protection from gender-based violence and modifying their attitudes at UNRWA centers in Syria - شروف, أنساب; شريبه, بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The current research aimed to measure the impact of a training program of workers in UNRWA centers in the Syrian governorates for developing their capacities in protection from gender-based violence based and modifying the attitudes. It also aimed to identify the differences in the level of worker’s capacities according to the nature of their work and their educational qualifications. The semi-experimental approach was followed and a questionnaire consisting of three dimensions (basic knowledge, trends and self-assessment) was used as a research tool. The research sample consisted of (23) workers in UNRWA centers, who were drawn by the intentional sampling method. The results of the research revealed the existence of a large impact size of (1,144) for the program in developing the capacities of the sample members in the field of protection from gender-based violence, and the size of a medium impact in adjusting trends, which amounted to (0.766). Self-evaluation, and a small effect of (0.417) in increasing the basic knowledge level. The results also showed that there are differences between the sample members according to the nature of their work after implementing the program, as the social researcher was more capable than the case manager in the field of protection from gender-based violence, and there were no differences between the sample members in their abilities after applying the program according to scientific qualification.